2018
DOI: 10.1590/1414-431x20176784
|View full text |Cite
|
Sign up to set email alerts
|

Ilex paraguariensis extracts extend the lifespan of Drosophila melanogaster fed a high-fat diet

Abstract: Studies have suggested that total energy intake and diet composition affect lifespan and ageing. A high-fat diet induces oxidative stress and affects the development of diseases. In contrast, antioxidants are capable of reducing its harmful effects. Yerba mate beverages are an important source of antioxidants, but there is scarce knowledge about their effects on suppressing fat accumulation. Here, we investigated the compounds present in yerba mate extracts and assessed their effects on Drosophila melanogaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
10
0
2
Order By: Relevance
“…This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS. This increase in the malondialdehyde level agrees with the result of Paula et al (2016), Saraiva et al (2018) and Colpo et al (2018) which showed an increase in the MDA levels of the `Harwich strain of D. melanogaster.…”
Section: Discussionsupporting
confidence: 92%
“…This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS. This increase in the malondialdehyde level agrees with the result of Paula et al (2016), Saraiva et al (2018) and Colpo et al (2018) which showed an increase in the MDA levels of the `Harwich strain of D. melanogaster.…”
Section: Discussionsupporting
confidence: 92%
“…Para avaliar os efeitos das diferentes dietas sobre o tempo de vida das moscas usamos o protocolo que foi descrito anteriormente por Peng et al (2009) com pequenas modificações propostas por Colpo et al (2018). Cada grupo de 20 moscas machos, de 2 a 3 dias, nascidas na dieta sólida para manutenção de estoque, foram expostas a DP e DE, sendo as moscas mortas contadas a cada 2-3 dias.…”
Section: Longevidadeunclassified
“…Anteriormente, relatamos os efeitos de compostos bioativos de plantas em relação a proteção contra o estresse oxidativo, aumento do tempo de vida e modificação de parâmetros bioquímicos relacionados ao metabolismo energético em D. melanogaster. Entre os compostos testados estão o extrato de erva-mate (Ilex paraguariensis)(COLPO et. al., 2018) e farinha de couve manteiga(Brassicaoleracea L. var.acephala) (COLPO et al, 2019).…”
unclassified
“…Studies in Drosophila have revealed several extracts and pure compounds that could reduce fat accumulation and ectopic fat distribution associated with several pathological conditions. For example, Ilex paraguariensis extract was suggested to reduce the detrimental effects of HFDs in Drosophila [162], while the extract’s metasaponins, phenolic compounds, and methylxanthines increased mean lifespan and reduced fat accumulation along with cholesterol levels [162]. Additionally, supplementation of HFDs with 4% nectarine increased lifespan and fecundity in female wild-type flies while it decreased the expression of several metabolic genes including the foxo transcriptional target Pepck and oxidative stress-related genes (e.g., peroxiredoxin).…”
Section: Dietary Supplements For Healthy Aging and As Interventions Imentioning
confidence: 99%